Microsafe (Oral Care) to Control COVID-19 Infection - Muamer Alshalah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental practice poses a possible risk of cross-infection with COVID-19 among patients, dentists, and theirassistants by direct saliva exposure and indirect contact. At Al-Kafeel Hospital in Karbala, Iraq, This studyhas focused on using Microsafe (Oral car) as a mouthwash product to COVID-19 control infection.Materials and Methods: One hundred people used the Microsafe (oral care) as a mouthwash productto prevent COVID-19 for two months. Fifty persons from Al-Kafeel Hospital staff (dentists) are fullycommitted to prevention measures, and fifty persons from the Al-Kafeel Hospital patients regularly attendhospital treatment. Not all patients can be guaranteed and apply these preventive measures.Results: After two months of using Microsafe (oral care) as a mouthwash, only eleven of the total patientswere affected with COVID-19. Only three of the hospital staff and eight patients were affected.